2021
DOI: 10.3389/fmed.2021.742703
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Diaphragm Thickness and Thickening: Reference Values and Limits of Normality When in a Seated Position

Abstract: Background: Diagnosing diaphragm dysfunction in the absence of complete paralysis remains difficult. The aim of the present study was to assess the normal values of the thickness and the inspiratory thickening of both hemidiaphragms as measured by ultrasonography in healthy volunteers while in a seated position.Methods: Healthy volunteers with a normal pulmonary function test were recruited. The diaphragmatic thickness was measured on both sides at the zone of apposition of the diaphragm to the rib cage during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 30 publications
6
56
1
3
Order By: Relevance
“…In agreement with previous studies, diaphragm thickness was larger in men than women 9,15,20 . The calculation of thickening ratio cancels out sex differences.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with previous studies, diaphragm thickness was larger in men than women 9,15,20 . The calculation of thickening ratio cancels out sex differences.…”
Section: Discussionsupporting
confidence: 91%
“…The larger variation in T max-insp compared to T end-exp is in accordance with other reports. 20 This may be attributed to variation in subjects' performance of the maneuver to take a deep breath and affects the level of diaphragm recruitment and the anatomical position of the diaphragm relative to the ultrasound probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observational study performed on patients suffering from persistent adverse health effects 3-4 months after severe COVID-19 pneumonia found that their diaphragm function was nonetheless essentially normal. The mean values of excursions and thicknesses were close to the normal values previously reported in healthy volunteers assessed while in a seated position (19,20). Furthermore, and as expected, men had larger excursions during deep breathing, and their hemidiaphragm thickness was increased compared to women.…”
Section: Discussionsupporting
confidence: 89%
“…Ultrasound imaging of the diaphragm is a non-invasive means of measuring diaphragm thickness and inspiratory thickening because an increase in diaphragm thickness leads to inspiratory strength ( Roussos et al, 1979b ; Boussuges et al, 2021 ). When applied by experienced users it provides reproducible results, with good inter- and intra-observer reliability ( Cohn et al, 1997 ; Schepens et al, 2015 ).…”
Section: Recent and Future Developmentsmentioning
confidence: 99%